Convergence theorems for uniformly quasi-Lipschitzian mappings. (30th March 2004) - Zhou, Haiyun; Kang, Jung Im; Kang, Shin Min; Cho, Yeol Je
Abstract : We prove some convergence theorems of the modified Ishikawa iterative sequence with errors for uniformly quasi-Lipschitzian mappings in metric spaces. Our results generalize and improve the corresponding results of Petryshyn and Williamson, Ghosh and Debnath, Liu, and many others.